Ursprungsherde und Ausbreitungswege von Pflanzen- und Tierzucht und ihre Abhängigkeit von der Klimageschichte.: Fortsetzung des Aufsatzes aus Band XI, Heft 2 - von Wissmann, Hermann (ERDKUNDE, 1957)
The author’s paper On the role of nature and man in changing the face of the dry belt of Asia (Chicago 1956) was based on those sections of C. O. Sauer’s book Agricultural origins and dispersals (1952) which deal with the origins and the spread of the domestication of animals and the cultivation of plants in the Old World. The present paper is concerned in more detail with these questions and with Sauer’s concept of a succession of creative culture hearths. These are understood as regions of inventions in the rearing of plants and animals which thus made man the lord of creation. The oldest of these centres of origin, it seems, were the forests along the rivers and coasts around the Bay of Bengal. Next came the savannas and wooded steppes of India, then the mountains north-west of India, around the Hindukush, and finally the highlands of Western Iran and Armenia. Each of these nuclei of cultural diffusion was based on the previous one. Each of them sent out waves of dissemination which may have caught up with each other or may have lost some cultural elements upon entering a different climatic region. From the latest of these hearths a next step led to the early civilization of the delta oasis of Mesopotamia. This region, however, is no longer a centre of origin of domestication but one of inventions in technology. We see thus that this main sequence of rising cultures ran from tropical forest through wooded steppe to subtropical highland including small desert oases. Then it reached the large river oases where major irrigation schemes needed collaboration, centralization, and mass labour, as well as specialization and intensification of labour. It was there where the plough and the cart were invented. The author tries to correlate parts of this succession of rising cultures with the history of Late Glacial and Postglacial climate. He bases his argument on the almost certain fact, newly established in particular by means of radiocarbon data, that the cold and warm periods of prehistoric times occurred simultaneously in different parts of the globe. The Two Creeks or Allerod interval, the Salpausselka or Mankato substage of glaciation (about 8800 to 8100 B. C.), the Thermal Maximum (about 5500 to 2500 B. C.) and the decreasing warmth during the following period (2500 to 800 B. C.), all were global phenomena. While the curves of annual temperatures thus run similarly in different parts of the globe, the curves of precipitation and humidity seem often to be out of phase in different zones We still know only a little about these as regards the climatic zones of Asia. In the whole region from Egypt and the northern Sahara and from eastern Europe to Inner Asia, however, the long span of time from the 9th to the early 5th millennium appears to have been drier than today. This long dry phase thus included two periods of great contrast: a cold and a warm part. In Mesopotamia, Iran, Turan and Central Asia, the period until about 2500 (or 2400) B. C. was probably also relatively dry. In Turan, according to Tolstom, it ended rather abruptly and was followed by a more humid phase the duration of which is unknown. This latter phase might be contemporaneous with Matthes’s Little Ice Age of the Great Basin region in the western U. S. A. (c. f. Deevey, 1953, p. 297). The planting of tubers and the domestication of dog, p’g and fowl seem to have had their origin amongst a population of fishers and shellfish gatherers in humid southern Asia (at least some time before 10,000 B. C., i. e. prior to the Two Creeks or Allerod interval). This culture spread along rivers and along the coasts, at first those of the Indian and the western Pacific Oceans. In most cases archaeological remains may therefore have been later drowned due to the eustatic rise of the sea level, or have become covered by river deposits. As a second stage, cultivation of seed crops, especially of millets (i. e. grasses with small seeds), and of beans and oil plants may have begun in a kind of ladang (milpa) shifting agriculture in the area of winterdry forest and savanna in India. However, the main areas where this Trockensavanne according to C. Troll) where the soil is rich and easy to work. Within these areas seed planting spread first in India, then in northern China and also in the belt which runs from southern Arabia westwards through the Sudan. Most or all millet species had their origin in these regions (c. f. p. 86) **) which are all situated south of the dry belt. The reason for this fact may be appreciated when one realizes that at about the 9th millennium northern Eurasia was cold (and had been cool before) and that the Sahara and Arabian deserts, as well as those of Iran, were drier than they are now. The Natufian of Palestine may have been a millet growing and hunting culture. The next steps in the main sequence seem to have been the domestications of sheep and of goats in the mountain regions adjacent to North-west India. This, together with the growing of millets and pulses and the breeding of dogs, pigs and fowls, may be considered a primary stage of a farming culture (Bauerntum). Because of its flocks of sheep and goats it could cross dry zones more easily. It may already have begun oasis irrigation (oldest strata of Jericho ?). One main route of its spread seems to have been that to Africa by way of South Arabia. It was probably during the millennia after the last cold period while the upper limit of trees and the snow line rose to greater heights than they reach now, that the highlands of Armenia and western Iran, stretching perhaps as far as Syria, became an important hearth of origin. Emer (TRITICUM DICOCCUM) and perhaps einkorn (TRITICUM MONOCOCCUM) were grown as the first wheat varieties, and the wild cattle were tamed and bred. This was the origin of a full farming culture which, however, still lacked the plough as well as broadcasting or drilling of seeds. When, during the 6th millennium, the upper limits of trees and cereals rose to a height perhaps 500 m. above their present one, these highlands became more favourable for farming than they are now; but they were surrounded by deserts drier than today in the north, east and south. The same conditions applied in the highlands around the Hindukush mountains. There the glaciers were smaller than now and the oases fed by glacier streams all along the foot of the highlands of Central Asia at the time must have been smaller and scarcer. A sheep breeding culture was able to spread over Tibet; there it began the cultivation of the wild six-rowed barley. The two-rowed barley had probably been cultivated earlier; but it is an open question whether this happened first in the region where emer originated or in the area around the Hindukush. The cultivation of the six-rowed barley spread over China and India. From India it probably found its way to South Arabia and Abyssinia and then to upper Egypt, where emer and six-rowed barley probably met during the 5th millennium. A sheep breeding culture may have spread northwards over the highlands of the Tien-shan to the Altai mountains and there may have stimulated the hunting tribes of the taiga (muskeg) forests to breed the reindeer (c. f. Hancar). The question is asked: May not the beginning of agriculture in the Nile and Euphrates deltas before 4000 B. C. be due to the fact that perhaps then, but not before this period, the deposition of both these rivers could counterbalance and even overcome a slackening eustatic rise of the sea leve? The desert of Turan at that time, more arid and less well provided with oases, served as a barrier between the hunters of the taiga and the northern steppes on the one side, and the agriculturalists and farmers of the oases and steppes of Iran and the Near East on the other. Farming of the wooded steppe spread rather quickly, however, across Asia Minor to south eastern and central Europe, where the Danubian culture arose probably at about 4000 B. C. In the period which began at 2500 B. C. when the climate became cooler and the snow line descended, when the firn fields of Central Asia began to grow and the glaciers began to advance, their melt water streams increased in size and the natural oases along the foot of the mountains became larger and more numerous. As, beginning at about 2500 or 2400 B. C. there was also a humid phase, this process was probably a fairly rapid one. It was as late as this period that the fishing and hunting people of the Amu delta began to breed cattle and sheep. An irrigation culture or civilization spread in the oases along the mountain foot of Turan and further to Hsinkiang. Towards the end of the 3rd millennium it introduced a coloured type of pottery into the seed-planting culture of North China which was probably still growing millets, barley and beans, and was breeding dogs, pigs and fowls. In the early second millennium an ingression of irrigation practising cultivators, which had spread along the chains of oases of Central Asia, introduced cattle into China. These people built strongly fortified villages and they may have started river control in the Hwangho delta. Elements of the lunar and chthonic beliefs of western Asia were introduced. This Lungshan civilization brought perhaps already the skill of writing with it. In the late 3rd millennium, when the desert of Turan had lost its function as a strong barrier, the advanced hunters of the north and the cultivators and the oasis civilization of the south were able to meet along an extensive border zone. It seems that an amalgamation resulted from this meeting and a new virile and vigorous culture was formed, in which, from the early second millennium B. C. onwards, the horse, the war chariot and (later on) the Indo- European peoples played an important role. Many of the processes suggested to have taken place in prehistory are still hypothetical. The same applies to some of the correlations with climatic history which in itself is partly still uncertain. Nevertheless the author is of the opinion that it is a point in favour of the sequence of creative centres of culture as submitted by Sauer and further developed in this paper, that it fits excellently together with the succession of cultures as presented by ethnologists, for instance by Dittmer. It has the further advantage of making the assumption of parallel inventions largely unnecessary. This sequence is one amazingly progressive chain of creative centres — or even one single centre that moved from southeast to northwest — in a wide space of relative stagnancy, a space of continents and coasts with heterogeneous climates, where elements of waves of dispersion which spread just from this progression of hearths were taken over or were transformed or rejected.